“Who Is Doing My Surgery?” Patient Preferences Regarding Trainee Involvement in Surgical Care - Moore, Daniel B.; Harris, David J., III; Coyne, Laura; Kryscio, Richard J.; Kang, Qiwen; Davis, Marla (Journal of Academic Ophthalmology, 2019)
Purpose There are no uniform standards to inform patients to what extent trainees are involved in their care. This may lead to inequities in sharing the potential risks associated with receiving care in an academic setting. This study was designed to determine patients' level of knowledge of the medical education system, their preferences regarding who provides treatment, and how strongly they would react if they found certain members of the care team were involved without their consent.Design This study is a prospective, nonrandomized, and observational survey of a convenience sample.Methods Consecutive patients referred for a cataract surgery evaluation to the Veteran's Affairs Ophthalmology Department in Lexington, KY between 2015 and 2017 were recruited.Results Ninety-six of 113 eligible patients (response rate 85%) completed the survey. About 33, 69, 33, and 49% of respondents recognized an intern, resident, fellow, and attending as a doctor, respectively. Three quarters (76.1%) felt it was important to be asked permission in advance of a resident assisting or performing surgery, and 21% indicated they would go elsewhere if they found that a resident would assist in, or perform their surgery. About 21, 21, and 58% of respondents would be upset or very upset if a resident was in the operating room, assisted in, or performed surgery without their permission, respectively.Conclusion This survey demonstrates an overall willingness of this specific, largely confined patient population to receive supervised care from training physicians provided they are fully informed and educated on the role of those involved in their care.
Keywords: informed consent; resident surgery; academic medicine; medical trainee